2004
DOI: 10.1039/b317003a
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic properties of uranyl crown ether complexes in non-aqueous solvents

Abstract: The spectroscopic properties of the complexes of uranyl with oxacrowns, azacrowns, thiacrowns of different ring size, polyethyleneglycols , and [2.2.1] and [2.2.2] cryptands were studied in acetonitrile and propylene carbonate solutions by absorption and luminescence spectroscopy. Depending on the ligand, marked differences in the fine structure of the spectra were observed. The crown ethers with six oxygen atoms (18-crown-6, dicyclohexano-18-crown-6, benzo-18-crown-6, dibenzo-18-crown-6 and [2,4]-dibenzo-18cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The free-energy analysis suggests that the binding of UO 2 2+ onto dibenzo crown ether (DBCE) and dicyclohexano crown ether (DCHCE) is favorable among the various crown ethers available. 17,18 Thus, DBCE and DCHCE would be ideal candidates for the adsorption of UO 2 2+ ions. The UO 2…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The free-energy analysis suggests that the binding of UO 2 2+ onto dibenzo crown ether (DBCE) and dicyclohexano crown ether (DCHCE) is favorable among the various crown ethers available. 17,18 Thus, DBCE and DCHCE would be ideal candidates for the adsorption of UO 2 2+ ions. The UO 2…”
Section: Introductionmentioning
confidence: 99%
“…Zolotov observed that polymerized crown ether enhances the adsorption of uranyl ions from the seawater using the metal binding reaction. The free-energy analysis suggests that the binding of UO 2 2+ onto dibenzo crown ether (DBCE) and dicyclohexano crown ether (DCHCE) is favorable among the various crown ethers available. , Thus, DBCE and DCHCE would be ideal candidates for the adsorption of UO 2 2+ ions. The UO 2 2+ binding or adsorption on the crown ethers have laid important understanding as these ions show competitive interactions with the solvent molecules and crown ethers .…”
Section: Introductionmentioning
confidence: 99%
“…Physicochemical properties of simple uranyl compounds have been widely studied in aqueous solution [4,9,10], in organic solvents [6,[10][11][12], and in the solid state [13,14]. Semi-empirical [15,16] and first-principles studies [17] have been essential to decipher the electronic and vibronic states, the nature of the chemical bonds in uranyl coordination compounds [18][19][20], as well as to model extraction mechanisms [21].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the luminescent properties of the uranium indicate that, for the longer PEG chains (PEG-300 and 400), inclusion complexes were formed, whereas for smaller chains, the organic molecule coordinates to the uranyl ion through its second coordination sphere. Despite the extensive use of crown ethers for the separation of lanthanide and actinide mixtures (Servaes et al, 2004), as well as the use of PEG-aqueous biphasic systems for similar purposes (Chen et al, 2005), there are few data describing stability constants for the coordination of UO 2 2+ with either crown ethers or PEG molecules in aqueous media. The only available formation energies or stability constants for U(VI) with crown ethers have been reported in organic solutions (Rounaghi and Heydari, 2008;Rounaghi and Kakhki, 2009).…”
Section: Solubility Considerationsmentioning
confidence: 99%
“…They observed an internal hydrogen bond between the oxygen atoms in positions O5 and O11, causing cyclising of the PEG molecule, which adopts a configuration similar to the crown ether complex. More recently, Servaes et al (2004) investigated the spectral properties of uranyl complexes with PEG-200, PEG-300 and PEG-400 in acetonitrile and propylene carbonate solutions. Changes in the luminescent properties of the uranium indicate that, for the longer PEG chains (PEG-300 and 400), inclusion complexes were formed, whereas for smaller chains, the organic molecule coordinates to the uranyl ion through its second coordination sphere.…”
Section: Solubility Considerationsmentioning
confidence: 99%